European academy of dermatology and venereology European prurigo project: expert consensus on the definition, classification and terminology of chronic prurigo - Pereira, Manuel P.; Weisshaar, Elke (Journal of the European Academy of Dermatology and Venereology, 2018)
Background The term prurigo has been used for many decades in dermatology without clear definition, and currently used terminology of prurigo is inconsistent and confusing. Especially, itch-related prurigo remains unexplored regarding the epidemiology, clinical profile, natural course, underlying causes, available treatments and economic burden, although burdensome and difficult to treat. Objective To address these issues, the multicentre European Prurigo Project (EPP) was designed to increase knowledge on chronic prurigo (CPG). In the first step, European experts of the EADV Task Force Pruritus (TFP) aimed to achieve a consensus on the definition, classification and terminology of CPG. Additionally, procedures of the cross-sectional EPP were discussed and agreed upon. Methods Discussions and surveys between members of the TFP served as basis for a consensus conference. Using the Delphi method, consensus was defined as an agreement ≥75% among the present members. Results Twenty-four members of the TFP participated in the consensus conference. Experts consented that CPG should be used as an umbrella term for the range of clinical manifestations (e.g. papular, nodular, plaque or umbilicated types). CPG is considered a distinct disease defined by the presence of chronic pruritus for ≥6 weeks, history and/or signs of repeated scratching and multiple localized/generalized pruriginous skin lesions (whitish or pink papules, nodules and/or plaques). CPG occurs due to a neuronal sensitization to itch and the development of an itch-scratch cycle. Conclusion This new definition and terminology of CPG should be implemented in dermatology to harmonize communication in the clinical routine, clinical trials and scientific literature. Acute/subacute forms of prurigo are separated entities, which need to be differentiated from CPG and will be discussed in a next step. In the near future, the cross-sectional EPP will provide relevant clinical data on various aspects of CPG leading to new directions in the scientific investigation of CGP.